2021
DOI: 10.3390/diagnostics11122214
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Texture Analysis of Carotid Plaque as Predictor of Unfavorable Outcome after Carotid Artery Stenting: A Preliminary Study

Abstract: Novel biomarkers are advocated to manage carotid plaques. Therefore, we aimed to test the association between textural features of carotid plaque at computed tomography angiography (CTA) and unfavorable outcome after carotid artery stenting (CAS). Between January 2010 and January 2021, were selected 172 patients (median age, 77 years; 112/172, 65% men) who underwent CAS with CTA of the supra-aortic vessels performed within prior 6 months. Standard descriptors of the density histogram were derived by open-sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Through radiomics or texture analysis, 10 studies tended to classify unstable or risk plaques ( 25 , 27 , 29 , 32 , 33 , 39 - 43 ). Moreover, 5 studies focused on predicting unfavorable cerebral and cardiovascular events ( 28 , 35 - 38 ), 2 on evaluating stenosis or in-stent restenosis ( 26 , 30 ), 1 on assessing the robustness of radiomics features ( 34 ), and 1 on evaluating the relationship between glycated hemoglobin and ultrasound plaque textures ( 31 ). The details are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through radiomics or texture analysis, 10 studies tended to classify unstable or risk plaques ( 25 , 27 , 29 , 32 , 33 , 39 - 43 ). Moreover, 5 studies focused on predicting unfavorable cerebral and cardiovascular events ( 28 , 35 - 38 ), 2 on evaluating stenosis or in-stent restenosis ( 26 , 30 ), 1 on assessing the robustness of radiomics features ( 34 ), and 1 on evaluating the relationship between glycated hemoglobin and ultrasound plaque textures ( 31 ). The details are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…All studies exhibited a low events per variable (EPV) value due to the large amount of candidate features and the limited carotid plaque samples. Regarding missing data, 12 studies conducted complete-case analysis and manually eliminated individuals without satisfactory images or clinical data or those who were lost to follow-up ( 25 , 26 , 28 - 30 , 32 , 36 - 41 ). In contrast, 7 studies did not describe how missing data were handled or the analytical procedures used to assess missing data ( 27 , 31 , 33 - 35 , 42 , 43 ), 4 studies lacked validation ( 28 , 30 , 31 , 39 ), and 2 studies had a high risk of bias in domain 1 for the stated inappropriate inclusion or exclusion criteria ( 33 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggested that the ultrasound characteristics of a vulnerable carotid plaque are strongly associated with complications after CAS. 8 Some researchers have pointed out that carotid hypoechoic plaque has predictive value for in-stent restenosis. 9 In addition, another study with a small sample size showed that plaques detected by contrast-enhanced ultrasound (CEUS) were significantly correlated with in-stent intimal hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…It obtains relevant parameters by analyzing images and has positive significance in the judgment and analysis of computed tomography (CT) images [ 14 , 15 ]. Texture analysis quantifies tissue heterogeneity by evaluating the texture roughness and distribution within the lesion, and it can evaluate the characteristics of the lesion in more detail, which is helpful for judging the characteristics of the tumor and evaluating the prognosis and metastasis [ 16 , 17 ]. Analyzing whether texture parameters correlate with disease metastases requires modeling.…”
Section: Introductionmentioning
confidence: 99%